Development of a tetraplex reverse transcription digital PCR (RT-dPCR) assay for three carlaviruses and an ilarvirus infecting hop and viral titer quantification in different tissue types - Herrera-Blitman, Natalia; Bloch, Melody; Helmick, Ericka; Harper, Scott; Vallad, Gary E; Bahder, Brian W (Plant disease, 2025)
The hop plant (Humulus lupulus) is an economically important perennial species of plant due to its role in beer production. While the majority of hop production occurs in central Washington State, local production in regions around the United States is gaining popularity due to local micro-breweries wanting to use locally grown hops in their production. In Florida, production has recently increased, and while most hop plants are grown from tissue culture, the development of a cost-effective diagnostic assay for hop viruses is critical to ensure planting material is clean. In this study, a tetraplex RT-dPCR assay was developed for the detection of four common hop viruses; Apple mosaic virus (ApMV), Hop mosaic virus (HMV), Hop latent virus (HLV) and American hop latent virus (AHLV). A synthetic control was generated with corresponding viral sequences inserted in tandem for optimization. Stem, petiole, and leaf tissue sampled from each of three different cultivars with different viral profiles were screened with the tetraplex RT-dPCR assay. Across all tissue types and cultivars, HLV had the highest titer level, followed by HMV and ApMV having the lowest levels. Additionally, there were significant levels of variation among tissue types across cultivars. These data highlight the utility of this assay for detecting viruses in hop tissue and provide a useful diagnostic tool for screening hop plants to confirm they are healthy. This assay will be utilized in vector studies but also integrated into diagnostic services.